Five genetic polymorphisms of cytochrome P450 enzymes in the Czech non-Roma and Czech Roma population samples - Dlouhá, Lucie; Adámková, Věra; Šedová, Lenka; Olišarová, Věra; Hubáček, Jaroslav A; Tóthová, Valérie (Drug metabolism and personalized therapy, 2020)
Objectives Cytochromes P450 play a role in human drugs metabolic pathways and their genes are among the most variable in humans. The aim of this study was to analyze genotype frequencies of five common polymorphisms of cytochromes P450 in Roma/Gypsy and Czech (non-Roma) population samples with Czech origin. Methods Roma/Gypsy (n=302) and Czech subjects (n=298) were genotyped for CYP1A2 (rs762551), CYP2A6 (rs4105144), CYP2B6 (rs3745274) and CYP2D6 (rs3892097; rs1065852) polymorphisms using PCR-RFLP or Taqman assay. Results We found significant allelic/genotype differences between ethnics in three genes. For rs3745274 polymorphism, there was increased frequency of T allele carriers in Roma in comparison with Czech population (53.1 vs. 43.7%; p=0.02). For rs4105144 (CYP2A6) there was higher frequency of T allele carriers in Roma in comparison with Czech population (68.7 vs. 49.8%; p<0.0001). For rs3892097 (CYP2D6) there was more carriers of the A allele between Roma in comparison with Czech population (39.2 vs. 38.2%; p=0.048). Genotype/allelic frequencies of CYP2D6 (rs1065852) and CYP1A2 (rs762551) variants did not significantly differ between the ethnics. Conclusions There were significant differences in allelic/genotype frequencies of some, but not all cytochromes P450 polymorphisms between the Czech Roma/Gypsies and Czech non-Roma subjects.
Keywords: dospělí; cytochrom P450 CYP2A6; Genotype; Female; Adult; ženské pohlaví; lidé; genotyp; Cytochrome P-450 CYP2D6; Cytochrome P-450 CYP2B6; Cytochrome P-450 CYP2A6; Cytochrome P-450 CYP1A2; Male; Czech Republic; polymorfismus genetický; cytochrom P450 CYP2B6; Česká republika; cytochrom P-450 CYP2D6; cytochrom P-450 CYP1A2; mužské pohlaví; Polymorphism, Genetic; Humans